Hubungan Tingkat Pengetahuan Setelah Pendidikan tentang Upaya Berhenti Merokok (UBM) dengan Tingkat Keterampilan Konseling Sebaya di SMKN 2 Bandar Lampung - Geta Okta Prayogi; Dyah Wulan Sumekar; Sutarto; Riyan Wahyudo (Medula, 2020)
Smoking is a bad habit that danger the smoker and the non smoker. In SMKN 2 Bandar Lampung, some students have started smoking. Therefore, it is urgent to conduct socialization and found anti-smoking agents. This research is aim to identify knowledge level after education of smoking cessation efforts and peer counseling skill level, and also strength of relationship between knowledge level and peer counseling skill level. The research used cross sectional method with one group posttest design about smoking cessation efforts and peer counseling skill. Sampling technique was total sampling. The research was carried out in May-June 2017 at SMKN 2 Bandar Lampung. Sample consists of 21 peoples. Data was obtained from knowledge questionnaires and skill checklist of peer counseling. The result showed that the majority of student had good knowledge (86%) and skills (90,5%). The result of bivariate analyze obtained p value=0,014<0,05 which means there is relationship between knowledge level and skill level. There was a significant relationship between knowledge level after education about smoking cessation efforts and peer counseling skill level in SMKN 2 Bandar Lampung.